KETERAMPILAN KOMUNIKASI SISWA KELAS VII SMPN 2 JEMBER DALAM PEMBELAJARAN IPA DENGAN MODEL PROBLEM BASED LEARNING PADA MATERI KALOR DAN PERUBAHANNYA - Mega Yuliya Wati; Izza Afkarina Maulidia; Irnawat Irnawat; Supeno Supeno (FKIP Universitas Jember, 2019)
Abstract: This study aimed to describe the communication skills by using model Problem-Based Learning (PBL). The sample was 32 VII-A grade students of SMP Negeri 2 Jember. The method of data collection is the observation and portfolio-assessment student participant worksheet. The observation checklist includes all indicators that the ability to communicate any questions or comments, work in teams, and clarity of voice during a presentation or presenting the results of the discussion. Data processing conducted through the process of data reduction, data presentation, and conclusion. The results showed that oral communication skills of students grade VII A has excellent communication skills. Oral communication skills aspects work together in groups has risen 87.5% in the excellent category, aspects of any questions students also increased to 65.62% in both categories, and in the aspect of voice clarity has increased, although still within the category that is good enough 53.12%. Keywords: communication skills, problem-based learning, natural science